Religious Tolerance and Multicultural Interactions Among Arabic, Chinese, and Malay Ethnicities in Palembang: A Sociological Perspective on Harmony and Social Integration - Choirun Niswah; Bety; Ahmad Rofiq; Rahmat Abdullah; Choiriyah (Jurnal Sosiologi Agama)
This research focuses on accommodating social interaction between Arab, Chinese (Chinese) and Malay groups as a model of multicultural education. This accommodative social interaction is very important because, without accommodative social interaction, different ethnic groups can't live together. This research answers the question of how accommodating social interaction between ethnic groups in Palembang is a multicultural education. This research method uses a qualitative approach to describe accommodative social interactions. Meanwhile, data collection techniques are carried out through interviews, observation and documentation. The research results show that accommodative social interaction is carried out by understanding religious and cultural values ​​between ethnic groups and implementing deliberative accommodation, positive law enforcement and tolerance.